2015
DOI: 10.1093/europace/euv350
|View full text |Cite
|
Sign up to set email alerts
|

Role of insertable cardiac monitors in anticoagulation therapy in patients with atrial fibrillation at high risk of bleeding

Abstract: In AF patients with high bleeding risk, ICM-guided rhythm control with AADs and assessment of AF burden may allow safe discontinuation of OACs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…An option for minimization of anticoagulant risk could be the transient use of oral anticoagulation linked to onset and offset of an episode of AF in patients at high risk of bleeding and low burden of AF. One such study used data from real-world practice setting in patients with AF and ICM devices [ 57 ]. Up to 87% of patients had a low AF burden, classified as presence of AF in <1% of the time and were therefore eligible to discontinue anticoagulation.…”
Section: Targeted Anticoagulation In Patients At High Risk Of Bleedinmentioning
confidence: 99%
“…An option for minimization of anticoagulant risk could be the transient use of oral anticoagulation linked to onset and offset of an episode of AF in patients at high risk of bleeding and low burden of AF. One such study used data from real-world practice setting in patients with AF and ICM devices [ 57 ]. Up to 87% of patients had a low AF burden, classified as presence of AF in <1% of the time and were therefore eligible to discontinue anticoagulation.…”
Section: Targeted Anticoagulation In Patients At High Risk Of Bleedinmentioning
confidence: 99%
“…Without an objective and continuous monitoring of cardiac rhythm by implantable devices, it is not easy to accurately determine the efficacy and adverse effects of AAD. Short-term rhythm monitoring with event monitor or Holter monitor for a period ranging from 1 week to 1 month may miss brief intermittent periods of AF or other arrhythmias [ 19 ]. Thus, continuous rhythm monitoring to detect episodes of AF recurrence and proarrhythmias/bradycardia potentially related to AAD was another important aspect of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Following ablation, the maximum daily burden was significantly reduced and the majority of patients had a maximum AF burden of <5 min/day. While medication was not collected consistently within this trial, recent studies have identified that utilizing continuous AF monitoring could be effective in management of antiarrhythmic and anticoagulation therapies for a selected group of patients …”
Section: Discussionmentioning
confidence: 99%